Linguistic Approach for Estimation of Electrocardiograms’s Subtle Changes Based on the Levenstein Distance - Fainzilberg, L.S.; Dykach, Ju.R. (Кибернетика и вычислительная техника, 2019)
The purpose of the article is to develop algorithmic and software components to solve this problem and conduct experimental studies on model and real data. Methods. ECG of certain groups was automatically encoded, Levenshtein distance was calculated between ECG pairs for group and the reference codogram of the group was constructed. The evaluation of the results of experimental studies was carried out on the basis of traditional methods of statistical analysis. Results. It is shown that based on the Levenshtein distance between all pairs of codograms of the test group, the reference codogram of the group of patients with coronary artery disease (CAD) and the group of healthy volunteers can be determined. It was established that making decisions based on the comparison of the ECG codogram of the person with the reference codogram allows for the separation of representatives of the indicated groups with sensitivity SE = 72% and specificity CP = 79% even in those cases when the traditional analysis of the ECG in 12 leads is not informative. Мета статті — розробити алгоритмічні і програмні компоненти для розв’язання цього завдання і провести експериментальні дослідження за модельними і реальними даними. Методи. Забезпено автоматичне кодування ЕКГ, обчислення відстаней Левенштейна між парами ЕКГ певної групи випробовуваних і побудова референтної кодограми групи. Оцінювання результатів експериментальних досліджень проводилося на основі традиційних методів статистичного аналізу. Результати. Показано, що на основі відстаней Левенштейна між усіма парами кодограм групи випробовуваних можна визначити референтну кодограму групи хворих на ішемічну хворобу серця (ІХС) і групи здорових добровольців. Встановлено, що прийняття рішень на основі порівняння кодограми ЕКГ випробуваного з еталонною кодограмою забезпечує поділ представників зазначених груп з чутливістю SE = 72% і специфічністю CP = 79% навіть в тих випадках, коли традиційний аналіз ЕКГ у 12 відведеннях виявляється неінформативним. Цель статьи — разработать алгоритмические и программные компоненты для решения этой задачи и провести экспериментальные исследования на модельных и реальных данных. Методы. Обеспечивалось автоматическое кодирование ЭКГ, вычисление расстояний Левенштейна между парами ЭКГ определенной группы испытуемых и построение референтной кодограммы группы. Оценка результатов экспериментальных исследований проводилась на основе традиционных методов статистического анализа. Результаты. Показано, что на основе расстояний Левенштейна между всеми парами кодограмм группы испытуемых можно определить референтную кодограмму группы больных ишемической болезнью сердца (ИБС) и группы здоровых добровольцев. Установлено, что принятие решений на основе сравнения кодограммы ЭКГ испытуемого с эталонной кодограммой обеспечивает разделение представителей указанных групп с чувствительностью SE = 72% и специфичностью CP = 79% даже в тех случаях, когда традиционный анализ ЭКГ в 12 отведениях оказывается неинформативным.